Rapid Diagnosis and Surgical Management of Catastrophic Stanford Type A Acute Aortic Dissection Resulting in Successful Lung Donation: A Case Report - Koki Yokawa; Ryota Abe; Tomonori Higuma; Kazunori Yoshida; Hidefumi Obo; Makoto Kadotani; Hidetaka Wakiyama (Clinical Case Reports, 2026)
ABSTRACT This case highlights that rapid diagnosis and emergency surgical repair for catastrophic Stanford Type A acute aortic dissection may preserve the opportunity for successful lung donation even when neurological recovery is impossible. Transthoracic echocardiography played a critical role in establishing the diagnosis when computed tomography could not be performed.